Lesion size and cystic morphology are key determinants of parathyroid hormone washout in primary hyperparathyroidism - Çordan, İlker; Aksu, Oguzhan (Frontiers in Endocrinology, 2025)
PurposeAccurate preoperative localization of parathyroid adenomas is of great importance to ensure targeted and effective surgical treatment of primary hyperparathyroidism (PHPT). In this context, parathyroid fine-needle aspiration biopsy (FNAB) performed under ultrasound guidance plays a crucial role. This study aimed to evaluate the relationship between ultrasonographic features of parathyroid adenomas and parathyroid hormone washout (PTH-WO) values.MethodsBetween January 2022 and August 2024, data from 128 parathyroid adenomas in 122 patients who were prepared for surgery due to PHPT and underwent ultrasound-guided FNAB along with PTH-WO testing were retrospectively evaluated. The obtained PTH-WO results were compared with B-mode and Doppler ultrasound findings.ResultsIn adenomas with a long axis greater than 10 mm and those containing cystic components, PTH-WO levels were found to be significantly higher (p = 0.005 and p = 0.02, respectively). Additionally, a positive correlation was identified between PTH-WO levels and the short and long axis dimensions of the adenomas. In contrast, no significant relationship was observed between PTH-WO levels and B-mode (grayscale) or Doppler (vascularity) ultrasound features.ConclusionPTH-WO values vary according to the ultrasonographic dimensions of parathyroid adenomas and are measured at higher levels in cystic adenomas. Other ultrasonographic features do not significantly affect PTH-WO levels. Therefore, the size of the lesion should be taken into account when interpreting PTH-WO results.